Cytotoxicity Evaluation of Algal Extracts Using three Sep-ART ArtemIa (INVE) Groups - Mehmet NAZ (Journal of Animal and Plant Sciences, 2026)
The study was conducted to determine the cytotoxic effects of different algal extracts on Artemia sizes and to assess how organism size influences sensitivity to algal bioactive compounds. The cytotoxicity of chloroform, acetone, methanol, hexane and ethanol extracts of five algal species (Chlorella sp., Sargassum sp., Spirulina sp., Ulva sp. and Schizochytrium sp.) on three Artemia groups (Sep-Art 430µm, Sep-Art 480µm and Sep-Art- 500µm) were investigated. Five concentrations (5000 µg/mL, 2500 µg/mL, 1000 µg/mL, 500 µg/mL and 100 µg/mL) of algal extracts were used in the study. In addition, the effects of different solvents on the extraction yields of the tested algae were revealed within the scope of the study. The experiment was conducted under a Completely Randomized Design (CRD) with three replicates for each treatment. When the LC50 values obtained from the study were classified, no highly toxic values (≤100 μg/mL) were observed. The results indicated that LC₅₀ values tended to decrease as Artemia size increased (Sep-Art 430 µm≤Sep-Art 480 µm≤Sep-Art 500 µm). The Sep-Art 500 µm group exhibited higher cytotoxic activity and mortality compared to the smaller size groups (p ≤0.05). Extraction yields varied significantly among solvents and algal species (p ≤0.05), with the highest yield observed in Chlorella sp. (methanol extract, 19.33 ± 0.003%) and the lowest in Ulva sp. (hexane extract, 1.62 ± 0.116%). In conclusion, no highly toxic effects (≤100 µg/mL LC₅₀) were observed in any of the three Artemia groups at different algal extract concentrations. The Sep-Art 430 µm group exhibited better stress tolerance than the Sep-Art 480 µm and Sep-Art 500 µm groups. The findings of this study, which evaluated the lethality test performances of three Sep-Artemia (INVE) groups, indicate that the Sep-Art 430 µm and Sep-Art 480 µm groups are suitable for use in Brine Shrimp Lethality Assay (BSLA) tests.
Keywords: Algae; Artemia; cytotoxicity; extraction yields; lethality